Development of a phase f physical education textbook based on the merdeka curriculum using the addie model - Eko Fibriono; M.E. Winarno; Siti Nurrochmah (Lambung Mangkurat University, 2026)
Background. The main problem in this study is the lack of adequate Physical Education (PE) teaching materials for Phase F that are aligned with the Merdeka Curriculum learning outcomes. This limitation results in learning that is not student-centered, and teachers struggle to provide independent guidance that is appropriate for the school’s available facilities and infrastructure. Objectives. The objective of this study is to develop valid, practical, and effective Phase F Physical Education teaching materials for the Merdeka Curriculum at State Senior High School 4 Malang. Method. This study employed the R&D model based on the Analysis, Design, Develop, Implement, Evaluate (ADDIE) framework. Data collection involved direct observation, interviews, and questionnaires, utilizing both qualitative and quantitative data analysis techniques. Results. Validation results from subject matter experts yielded a score of 92% and from media experts, 94%, indicating that the textbook is highly valid in terms of content, presentation, and visual design. Additionally, the small-group pilot test yielded a percentage of 83.8% (categorized as “highly suitable/practical”), and the large-group pilot test yielded 88.2% (categorized as “highly suitable/effective”). Conclusion. Based on these results, it can be concluded that the Physical Education textbook is highly suitable, practical, and effective for use in learning activities. This textbook, which contains four chapters of content, visual images, integrated QR codes, and Student Activity Sheets (SAS), makes a significant contribution to facilitating differentiated learning and supporting students’ independence in movement literacy in accordance with the philosophy of modern physical education.